The tool steel guide - Szumera, James A. (Industrial Press, 2003)
Annotation The Tool Steel Guideis an excellent aid and reference for all tool designers, tool and die makers, machinists and apprentices. It is packed with specifications, heat treatments and applications of all types of die and mold steels, as well as ideas and suggestions on how to prepare steels for machining and heat treatment. You will also find helpful information about avoidance techniques in design, finishing, grinding, electrical discharge machining and welding. This handy and convenient guide will go a long way in helping you dispel the air of mystery that for many years seems to have surrounded the selection, heat treatment and use of tool steels. Easy to read and understand. Explains the constituents of all the tool steels and the benefits or reasons they are used and how they affect performance. Provides information on how to choose the right tool steel for a given application. Discusses the heat treatment process for the different groups of tool steels. Addresses the proper methods for machining and grinding to avoid premature failure. Includes a special section on welding procedures of tool steels.
Includes index.
Keywords: Tool-steel -- Handbooks, manuals, etc.; elektronické knihy; electronic books